TINJAUAN PELAKSANAAN HANDOVER DI RUMAH SAKIT: TINJAUAN PUSTAKA: Overview of The Implementation of Handover in Hospital: Literature Review (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2021)
Background: Handover is an activity to deliver and receive reports regarding the patient's condition. Handover implementation consists of three stages, namely the preparation stage, implementation stage and post handover. Handover as an important element in providing nursing care and has a role in patient safety. Purpose: This study aims to identify the results of previous studies regarding the stages of implementing nurse handovers in hospitals. Methods: The method used in this study is a literature review with an assessment using the JBI Critical Appraisal Checklist for Analytical Cross Sectional Studies. Search using Google scholar and Library of the Faculty of Nursing-UM. Keywords used are nurse AND handover OR weigh accept. Results: Based on the five articles that have been reviewed, the overall description of the implementation of the handover is one article with a sufficient category, one article with a good category and three articles with an average implementation of the value range from 50% to 75.71%. The four articles used three stages of handover, namely preparation, implementation and post handover with the lowest score at the post handover stage with a value range of 14.5% to 38.8% and the highest value at the implementation stage of 59.4% -88%. One article uses five stages, namely the preparation, introduction, information exchange, observation and safety scan stages with the lowest range in the scan scan stage of 51.24% and the highest value at the introduction stage of 94.33%. Conclusion: Handover activity is influenced by the efficiency of time and human resources. Nurses are advised to carry out handovers in accordance with the SOP and carry out handovers using the SBAR effective communication format with the beside handover